Groundwater Single- and Multiobjective Optimization Using Harris Hawks and Multiobjective Billiards-Inspired Algorithm - AbdolGhafour Gerey; Amirpouya Sarraf; Hassan Ahmadi (Shock and Vibration)
This is the first attempt to combine the Multiobjective Billiards-Inspired Optimization Algorithm (MOBOA) with groundwater modelling to determine pumping rates within a well-distributed range of Pareto options. In this study, in order to determine an optimum solution for groundwater drawdown, pumping rates were selected accompanied by three minimization objectives: minimizing shortage influenced by inability to supply, adjusted shortage index, and minimizing the degree of drawdown within predefined areas. To optimize hydraulic conductivity and specific yield parameters of a modular three-dimensional finite-difference (MODFLOW) groundwater model, the Harris Hawks optimization algorithm was used to minimize the sum of absolute deviation between observed and simulated water-table levels. MOBOA was then utilized to optimize pumping rate variables for an Iranian arid to semiarid groundwater environment using these parameters. As the study results, when the maximum and minimum aquifer drawdown was specified in the range of −40 to +40 cm/year, the Pareto parameter sets produced satisfactory results. Overall, the “Simulation-Optimization-Modelling” protocol was able to generate a series of optimal solutions that were shown on a Pareto front. The study concluded to an optimum approach that provides policy makers in the Iranian water stressed zones with safe groundwater management alternatives.